Expert Answers
jeew-m eNotes educator| Certified Educator

`5c^2-39c-8`

`= 5c^2-40c+c-8`

`= 5c(c-8)+1(c-8)`

`= (c-8)(5c+1)`

So by grouping `5c^2-39c-8 = (c-8)(5c+1)`

atyourservice | Student

`5c^2-39c-8`

Multiply `a xx c`  `a=5`  `b=-39` `c=-8`

`5xx-8 = -40 ` then find factors of -40 that minus to -39

these numbers will be -40 and 1, plug them into the problem

`5c^2-40c+1c-8` now group the numbers and find the highest number they have in common

`(5c^2-40c)(1c-8)`

`5c(c-8) 1(c-8)`

`(5c+1)(c-8)`